2005
DOI: 10.1111/j.1460-9568.2005.04136.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere embolism‐induced cortical cholinergic deafferentation and impairments in attentional performance

Abstract: Ischemic events have been hypothesized to play a critical role on the pathogenesis of dementia and the acceleration of cognitive impairments. This experiment was designed to determine the consequences of microvascular ischemia on the cortical cholinergic input system and associated attention capacities. Injections of microspheres ( approximately 50 microm diameter; approximately 5000 microspheres/100 microL) into the right common carotid artery of rats served as a model of microvascular ischemia and resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 106 publications
(154 reference statements)
2
9
0
Order By: Relevance
“…This hypothesis is consistent with the results of experiments which demonstrated that rats are impaired in the acquisition and retention of high attentionally demanding spatial tasks [82][83][84][85][86]. In addition, studies in rodents [3,50,54] and monkeys [42,54] have demonstrated that selective loss of BF cholinergic nuclei does not disrupt mnemonic abilities but rather indicate attentional defects in learning and memory tests [36,87]. Our results may suggest that the very selective difference observed in OLT could be explained by differences in attentional processes which are enhanced due to protective action of NGF on cholinergic system.…”
Section: Discussionsupporting
confidence: 76%
“…This hypothesis is consistent with the results of experiments which demonstrated that rats are impaired in the acquisition and retention of high attentionally demanding spatial tasks [82][83][84][85][86]. In addition, studies in rodents [3,50,54] and monkeys [42,54] have demonstrated that selective loss of BF cholinergic nuclei does not disrupt mnemonic abilities but rather indicate attentional defects in learning and memory tests [36,87]. Our results may suggest that the very selective difference observed in OLT could be explained by differences in attentional processes which are enhanced due to protective action of NGF on cholinergic system.…”
Section: Discussionsupporting
confidence: 76%
“…41,42 In experimental studies, injection of 50-m microspheres into rat carotid arteries resulted in cerebral injury and reduced attentional performance. 43 Manipulation of the carotid artery during surgical or endovascular revascularization causes atheroembolization with consequent silent cerebral microinfarction. 44 Transcranial Doppler monitoring has identified approximately 1000 microemboli during CAS while CEA is associated with eight to 17 times fewer microemboli.…”
Section: ™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™mentioning
confidence: 99%
“…Cerebrovascular insufficiency has been associated with cholinergic and cognitive impairments (Craft et al, 2005), prompting us to examine these parameters in TGF mice featuring cerebrovascular dysfunction. Both the total number of ChAT-positive fibers and terminals ( Figure 5A), as well as the number of perivascular ChAT terminals ( Figure 5B) were comparable between elderly TGF mice and wild-type littermates, and pioglitazone had no effect, indicating the absence of a cholinergic deficit in aged TGF mice, at least with regard to this immunohistochemical assessment.…”
Section: Preserved Cholinergic and Cognitive Indices In Elderly Tgf Micementioning
confidence: 99%
“…We specifically studied arterial responsiveness and proteins regulating vascular structure or function. We also measured the neuronally driven cerebral glucose uptake (CGU) and CBF responses to whisker stimulation, the status of astrocytes involved in synaptic transmission and neurovascular coupling (Haydon and Carmignoto, 2006), cortical cholinergic innervation, not only known for its effect on cognition and CBF but also for its susceptibility to ischemia (Craft et al, 2005), and spatial memory in the Morris water maze. Our results provide new insights into the link between cerebrovascular dysfunction and dementia, and support the use of pioglitazone as a strategy to preserve the cerebral circulation in the context of advanced age, fibrosis, and antioxidant resistance, hence to potentially delay disease progression in vulnerable populations or to improve response to AD therapies.…”
Section: Introductionmentioning
confidence: 99%